Aceh ornaments exploration as ideas of contemporary building form through digital transformation / Zulhadi Sahputra, Muhammad Heru Arie Edytia and Mirza - Sahputra, Zulhadi; Edytia, Muhammad Heru Arie; Mirza, Mirza (2018)
Aceh is one of the Provinces that is rich in motives and ornaments. The richnes of Aceh motives and ornaments can be observed in Aceh craft works such as perforative art crafts at Rumoh Aceh, hand-weaving crafts, embroidery crafts, and plaiting crafts found all arround different parts of Aceh. These ornaments can inspire creative ideas of the developing contemporary building oriented in locality.One approach to develop creative and innovative exploration of ornaments is by utilizing fractal methods. The use of jBatik software as one of the innovations in digital technologies can be used as tools in the process of exploration and transformation of Aceh ornaments with fractal method approach. The use of jBatik software is considered suitable to create similar pattern or motives observed between Aceh ornaments and batik.The chosen study case in this study was the development of the terminal building of Sultan Iskandar Muda Airport in Aceh. The steps of transformation process are: analysis and improvement of ornament geometry, interpretation of fractal principles on ornaments, interpretation of ornament variants with jBatik and exploration of interpretation results of ornament with fractal application. The application of ornament transformation into architectural design is done in 3 ways, i.e. development of alternative design of building study case, application of ornament exploration in designs, and finalization of the designs. Aceh ornament exploration through this digital transformation process is expected to re-actualize the traditional architectural heritages into a contemporary context and to contribute in the enrichment and preservation of local ornaments using technologies